Conduit formation and crustal microxenolith entrainment in a basaltic fissure eruption: Observations from Thríhnúkagígur Volcano, Iceland - Michael R Hudak; Maureen D Feineman; Peter C LaFemina; Halldór Geirsson; Samuele Agostini (Volcanica, 2022)
Thríhnúkagígur Volcano, Iceland, is a composite spatter cone and lava field characteristic of basaltic fissure eruptions. Lava drainback at the end of the eruption left ~60 m of evacuated conduit, and a 4 × 104 m3 cave formed by the erosion of unconsolidated tephra by the feeder dike. Field relationships within the shallow plumbing system provide three-dimensional insight into conduit formation in fissure systems. Petrographic estimates and the relative volumes of the cave and erupted lavas both indicate xenolithic tephra comprises 5–10 % of the erupted volume, which cannot be reproduced by geochemical mixing models. Although crustal xenolith entrainment is not geochemically significant, we posit that this process may be common in the Icelandic crust. The Thríhnúkagígur eruption illustrates how pervasive, poorly consolidated tephra or hyaloclastite can act as a mechanically weak pre-existing structure that provides a preferential pathway for magma ascent and may influence vent location.